Assessment of carbapenem‐resistant Enterobacteriaceae—plate formula and quality control procedure. Issue 12 (9th November 2020) - Tran, Thanh C.; Pham, Binh T.; Pham, Van H.; Ngo, The A.; Hanberger, Håkan; Larsson, Mattias; Olson, Linus
Abstract: Aims: To assess a cost‐effective in‐house selective plate formula for actively screening carbapenem‐resistant Enterobacteriaceae (CRE). Methodology and results: The in‐house formula included CHROMagar TM Orientation, meropenem, and ingredients present in the Mac‐Conkey formula, such as bile salts and crystal violet (pH 6.9‐7.2). American Type Culture Collection strains and 200 clinical strains were used to validate the plate formula. The CRE plates had a sensitivity of 97.4% and a specificity of 98.8% with ATCC andor clinical strains used in the quality control procedure. A point prevalence survey among the 18 inpatients at Viet‐Tiep hospital ICU using fecal swabs plated at the in‐house agar plate showed a CRE prevalence of 44.4%. Conclusion: The in‐house plate had high sensitivity and specificity, particularly for Escherichia coli and the KESC group ( Klebsiella spp ., Enterobacter spp ., Serratia marscescens, and Citrobacter spp .), and it may be widely applied as an alternative to other ready‐to‐use commercial plates. Significance and impact of the study: The formula developed in the present study may facilitate the early detection and isolation of CRE and decrease transmission, particularly in low‐ and middle‐income countries with a high rate of CRE colonization and limited access to ready‐to‐use commercial plates. Abstract : This study has developed a low‐cost formula and quality control of a new agar plate for carbapenem‐resistant Enterobacteriaceae (CRE) screening. It can be applied where a large number of plates need to be used to find multi‐resistance on patients in the community and at hospitals before admission, and avoid transmission of CRE. a) Escherichia coli b) Klebsiella pneumoniae .